THE DYNAMIC OF POWER RELATION IN SHAPING JEMIMA STARLING SUBJECTIVITY IN THE STARLING GIRL 2023 THROUGH FOUCAULDIAN THEORY - Nur Qomariah; Maya Sekartaji (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2026)
This research analyzes the dynamic of power relations depicted in The Starling Girl (2023) through the lens Power Relations theory by Michel Foucault. This research aimed to identify how discourse, disciplinary power, pastoral power, panopticon and resistance operates as a foundational control mechanism and shaping Jemima’s subjectivity within Christian Conservative Community. The result of the study describes five mechanisms of power relation in the film that are operated in the religious communities that constructed the main character’s subjectivity from the obedient girl becoming a sinner and forgiven subject until resistant subject.